The Sacco Gang - Camilleri, Andrea (Europa Editions, 2018)
"Raffadali, province of Agrigento, 1920s. The Sacco brothers are free men with strong ideas about Socialism and the State. Their lives change radically one morning when their father, Luigi Sacco, receives an anonymous letter from the local Mafia demanding protection money. Luigi tells the police of the extortion letters, but the police don't know what to do: no one in the village has ever dared denounce the Mafia before. From that moment on, the Sacco brothers must defend themselves from the Mafia, from the authorities, from the Fascist state, from collaborators, traitors, and their neighbors as they are assailed by murder attempts, false accusations, and false testimony, traitors, and from the village's leaders, as they are assailed by murder attempts, false accusations, and false testimony"--Inside front cover.